Bioaccessibility of Chlorogenic Acid and Curcumin Co-Encapsulated in Double Emulsions with the Inner Interface Stabilized by Functionalized Silica Nanoparticles - Gimenez-Castillo, B; Paredes-Toledo, J (Elsevier Ltd, 2024)
The aim of this study was to evaluate the bioaccessibility of chlorogenic acid (CA) and curcumin co-encapsulated in Pickering double emulsions (DEs) with the inner interface stabilized by hydrophobically modified silica nanoparticles with myristic acid (SNPs-C14) or tocopherol succinate (SNPs-TS). Both SNPs-C14 and SNPs-TS showed contact angles > 90°. Pickering W1/O emulsions were formulated with 4 % of both types of SNPs. Pickering DEs showed higher creaming stability (5–7 %, day 42) and higher CA encapsulation efficiency (EE; 80 %) than control DE. The EE of curcumin was > 98 % in all the DEs. CA was steadily released from Pickering DEs during digestion, achieving bioaccessibility values of 58–60 %. Curcumin was released during the intestinal phase (∼80 % bioaccessibility in all DEs). Co-loaded DEs showed similar bioaccessibility for CA and curcumin than single-loaded. SNPs-C14 and SNPs-TS were suitable to stabilize the W1:O interface of DEs as co-delivery systems of bioactive compounds with health-promoting properties. © 2024 Elsevier Ltd